Efektivitas Ekstrak Serbuk Kayu Jati dan Mahoni Sebagai Pestisida Nabati untuk Mengendalikan Hama Kutu Putih pada Bibit Sengon (Falcataria moluccana): Effectivity of Teak and Mahogany Wood Extracts as Botanical Pesticide to Control Pseudococcus calceolariae Pests at Falcataria moluccana Seedlings - Kusumaningsih, Karti Rahayu; Woesono, Hastanto Bowo; Duru, Anastasya (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
Waste of teak and mahagony woods in the form of sawdust has not been utilized. Those woods contain of extractives subtances such as carbamic acid, ammonium carbamate, phenol, flavonoid, saponin, etc. which potential to be used as botanical pesticide to control pests. The purpose of this research is to know effectivity of teak and mahagony wood extracts as botanical pesticide with several solution formulas, to control Pseudococcus calceolariae pest at Falcataria moluccana seedlings. Teak and mahagony sawdust were extracted with ethanol solvent and made into botanical pesticide with 10%, 20% and 30% formulas. The observed parameters are decrease of incidency and severity of P. calceolariae attack at F. moluccana seedlings after botanical pesticide application. Results of the research showed that teak and mahogany wood extracts were effective to control Pseudococcus calceolariae pest at Falcataria moluccana seedlings. Teak wood extract with 30% formula gived higher incidency and severity decreased of P. calceolariae attack, with decrease of incidency and severity were 89.32% and 94.44%.